Liquid Smoke and Hydrogel Membrane as Burn Wound Healing Properties - Rayhan, Amar (Diponegoro International Medical Journal, 2023)
Background : Anyone has the potential to get injured, especially burns. Hydrogel membrane and liquid smoke are a combination of antibacterial, anti-inflammatory and antioxidant properties. These properties play an important role in wound healing. In wound healing, the re-epithelialization process is a critical parameter for the success of wound closure.Aim : Analyzed the effect of re-epithelialization length on burns of rats given a liquid smoke combination hydrogel membrane.Methods : Experimental research used post test only with control group design. The number of samples was 15 white wistar rats with burns which were divided into two treatment groups, namely P1 (liquid smoke combination hydrogel membrane), P2 (liquid smoke) and one control group K (hydrogel membrane). Assessment of reepithelialization length has been calculated using a microscope. Statistical test using One Way ANOVA – Post Hoc Bonferroni test.Results : The average length of re-epithelialization (µm) for each group was (P1) 2004.91, (P2) 1534.15 and (K) 1248.16. Based on the results of the One Way ANOVA analysis, we found p value  = 0.028 (p <0.05). This shows that there were significant differences in the data between groups.Conclusions : There was a significant difference on the length of re-epithelialization in rats burn wound between hydrogel membrane group with liquid smoke, liquid smoke group and control group.